LEGAL ISSUES FOR ELECTRONIC DOCUMENTS WORKFLOW REGULATION - K. Kussainova, Ainur; O. Kussainov, Duman; S. Zhumagulov, Bolat; K. Simtikov, Zhomart; O. Zhangutin, Baurzhan (Law, State and Telecommunications Review, 2020)
Purpose ”“ The main purpose of the paper is to analyze the problems of legal regulation of relations in the field of electronic document management. Methodology/approach/design ”“ The paper employs methods of comparative law and analytical, which determine the possibility of integrating international standards for the regulation of electronic document flow. Findings ”“ Electronic document flow is becoming an integral part of the most diverse areas of economic activity of any enterprise. The document flow contains elements of the general law of regulation and reaffirms the necessity of following specific instructions. Its electronic form allows the information interchange between subjects of economical and legal activity. This defines the possibility of the formation of a separate branch of legal regulation in the document flow. The possibility of the structuring and correlation of an informational and another branch of the law for the aim of complex usage of an electronic document flow is viewed as a separate aspect. Practical implications ”“ Material of the article may be useful in matters of regulation of the legislative system of document management. Originality/value ”“ The novelty of the study is that the article examined in detail the mechanism of electronic document management in different countries.